2014
DOI: 10.1371/journal.pone.0106161
|View full text |Cite
|
Sign up to set email alerts
|

TIMP-3 Expression Associates with Malignant Behaviors and Predicts Favorable Survival in HCC

Abstract: The tissue inhibitors of metalloproteinases (TIMPs) are proteins that specifically inhibit the proteolytic activity of the matrix metalloproteinases (MMPs). TIMP-3, the only member of the TIMPs that can tightly bind to the extracellular matrix, has been identified as a unique tumor suppressor that demonstrates the ability to inhibit tumor angiogenesis, invasion, and metastasis. This study aimed to detect the expression of TIMP-3 in hepatocellular carcinoma (HCC) and investigate the association between TIMP-3 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…Recent studies have identified TIMP3 as a tumor suppressor as its expression is silenced in malignant tumors including hepatocellular carcinoma (HCC) 18 , 19 . To evaluate the role of hepatic Timp3 overexpression in HCC, we have used a model of diethylnitrosamine (DEN) administration combined with dietary induced obesity.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have identified TIMP3 as a tumor suppressor as its expression is silenced in malignant tumors including hepatocellular carcinoma (HCC) 18 , 19 . To evaluate the role of hepatic Timp3 overexpression in HCC, we have used a model of diethylnitrosamine (DEN) administration combined with dietary induced obesity.…”
Section: Resultsmentioning
confidence: 99%
“…Yu J et al linked the circRNA cSMARCA5/miR-17-3p/miR-181b-5p/TIMP3 regulatory pathway to EMT in HCC [125]. TIMP3 has been reported to be a tumor cell suppressor in several studies and inactivates the EMT program [126,127]. It has been found that the decrease in circRNA cSMARCA5 facilitates HCC cell migration and metastasis and downregulates TIMP3 transcription by absorbing miR-17-3p and miR-181b-5p [125].…”
Section: Other Pathways Related To Circrnasmentioning
confidence: 99%
“…Immunohistochemical (IHC) analysis was performed as described previously. [ 47,48 ] In brief, formalin-fi xed, paraffi n-embedded tissues from the mice were prepared and paraffi n sections were incubated with a primary TIMP3 Rabbit mAb (Cell Signaling Technology, USA) in PBS, washed and then incubated with a horseradish peroxidase-conjugated antibody (Santa Cruz Biotechnology, CA, USA). Negative controls were included by replacement of the primary antibody with PBS.…”
Section: −1mentioning
confidence: 99%